The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.schres.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

A stress-coping model of mental illness stigma: I. Predictors of cognitive stress appraisal

Abstract: Stigma can be a major stressor for individuals with schizophrenia and other mental illnesses. It is unclear, however, why some stigmatized individuals appraise stigma as more stressful, while others feel they can cope with the potential harm posed by public prejudice. We tested the hypothesis that the level of perceived public stigma and personal factors such as rejection sensitivity, perceived legitimacy of discrimination and ingroup perceptions (group value; group identification; entitativity, or the percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
1
11

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(159 citation statements)
references
References 35 publications
3
141
1
11
Order By: Relevance
“…A study by Rüsch et al (2009a) provides some support for these hypotheses. They reported stress appraisal was positively correlated with rejection sensitivity.…”
Section: Situational Modelsmentioning
confidence: 89%
See 2 more Smart Citations
“…A study by Rüsch et al (2009a) provides some support for these hypotheses. They reported stress appraisal was positively correlated with rejection sensitivity.…”
Section: Situational Modelsmentioning
confidence: 89%
“…Associating with 'the own' (people who are similarly stigmatised) can be a comfort, being around people who are accepting and have shared experiences (Knight, et al, 2003). Group identification has been linked to more perceived coping resources (Rüsch, et al, 2009a). Unfortunately, this study did not use measures that identified what these were.…”
Section: Factors That Influence How People Cope With Stigmamentioning
confidence: 93%
See 1 more Smart Citation
“…Across various psychiatric disorders, greater RS is associated with greater perceived social stress and fewer perceived coping resources (Rusch et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…It may, for instance, result in depression or post-traumatic stress disorder (PTSD) [2]. To make things even worse, such stressrelated disorders stigmatize the people suffering from them, which in itself is an additional stressor [42,43].…”
Section: Introductionmentioning
confidence: 99%